Physical therapy for children with cerebral palsy : an evidence-based approach - Rahlin, Mary, 1962- (Thorofare, NJ : SLACK Incorporated, 2016)
Cerebral palsy is the most common movement disorder encountered in pediatric physical therapy practice. Physical Therapy for Children With Cerebral Palsy: An Evidence-Based Approach is a unique, comprehensive reference that focuses on physical therapy management of children with cerebral palsy through the analysis and synthesis of published research, and it offers learning opportunities to a wide reading audience.
Theoretical perspectives on motor development -- Variability, complexity, and adaptability in typical and atypical motor development -- Definition, incidence, etiology, classification, and diagnosis of cerebral palsy -- Alterations in body structures and functions, activity limitations, and participation issues in children with cerebral palsy -- Evidence for prognosis for ambulation, employment, and independent living -- The interdisciplinary team and effective interprofessional collaboration in health care / Mary Rahlin and Wendy Rheault -- neurological and neuromuscular systems : medical and surgical management of alterations in body structures and functions -- Musculoskeletal system : medical and surgical management of alterations in body structures and functions -- Cardiovascular and pulmonary, digestive, integumentary, urogenital, and sensory systems : medical and surgical management of alterations in body structures and functions -- Pain assessment and management / Roberta Henderson and Mary Rahlin -- Physical therapy examination and evaluation : tests and measures, anticipated goals, expected outcomes, and tracking progress -- Therapy settings and service delivery models -- Assessment and management of therapy-related behavior -- Therapeutic approaches / Regina T. Harbourne and Mary Rahlin -- Common intervention strategies and techniques -- Complementary and alternative interventions -- Significance of manual guidance in pediatric physical therapy practice -- Therapy frequency, duration, and intensity issues -- Normal gait kinematics and kinetics / Elaine Owen -- Common approaches to orthotic management of the lower extremity, trunk, and upper extremity / Donald McGovern and Mary Rahlin -- Segmental kinematic approach to orthotic management : ankle-foot orthosis/footwear combination / Elaine Owen -- Assistive technology, with emphasis on positioning and mobility equipment -- Cerebral palsy as a life span condition -- Planning transition to adult life / Donna Frownfelter and Mary Rahlin.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Added to collection customer.56279.3
Keywords: Cerebral Palsy -- therapy; Physical Therapy Modalities; Evidence-Based Practice; Child; Cerebral palsied children -- Rehabilitation; Physical therapy for children; Electronic books